«O inferno é o real absoluto»: notas sobre as vanguardas tardias em Barcelona e Lisboa - Izabela Leal (Catalonia)
This essay aims at establishing the relations between the avant-garde movements that took place in Lisbon and Barcelona in the late 1940s, having as a basis the year of 1948. In Lisbon, the year was marked by Mário Cesariny’s break with the Surrealist Group of Lisbon and the formation of a new group called The Surrealists. In Barcelona, that same year, we have the emergence of the Catalan avant-garde group Dau Al Set, which had Joan Brossa as one of its founding members, as well as the release of a magazine by the same name. It is interesting to note that these late avant-garde movements developed in highly unfavorable political contexts, in Portugal during the Salazar dictatorship and in Spain under the Franco regime. As such, I intend to discuss the interventional and resistance aspects represented by these two artistic movements.